2021
DOI: 10.3390/su13073791
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Management Studies: A Systematic Literature Review

Abstract: In 2020, the whole world had to face a pandemic with inevitable profound changes in all aspects of life, from the social to the economic sphere. The profound economic crisis that followed the rise of the pandemic has pushed firms and researchers to question the necessary changes and new challenges for the survival of businesses. In this scenario, the aim of the paper is to analyze and classify the main contributions published on the topic of COVID-19 in managerial literature, seeking to discover the perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 202 publications
(147 reference statements)
2
24
0
3
Order By: Relevance
“…While approximately 30% of the articles reviewed within the scope of the current study were conducted as empirical qualitative studies, a significantly high 56.5% of all 246 most-cited articles were theoretical studies. In a study conducted by Piccarozzi et al [71], theoretical articles on COVID-19 totaled 45%, while 55% were empirical qualitative studies. Additionally, Fidahic et al [72] stated that researchers showed increased interest in publishing articles on the COVID-19 outbreak compared to previous coronavirus outbreaks (i.e., SARS-CoV and MERS-CoV).…”
Section: Resultsmentioning
confidence: 99%
“…While approximately 30% of the articles reviewed within the scope of the current study were conducted as empirical qualitative studies, a significantly high 56.5% of all 246 most-cited articles were theoretical studies. In a study conducted by Piccarozzi et al [71], theoretical articles on COVID-19 totaled 45%, while 55% were empirical qualitative studies. Additionally, Fidahic et al [72] stated that researchers showed increased interest in publishing articles on the COVID-19 outbreak compared to previous coronavirus outbreaks (i.e., SARS-CoV and MERS-CoV).…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic has disrupted the normal operating order of enterprises as well as employees' work rhythm. Consequently, employees might have faced greater challenges during this period (Piccarozzi et al, 2021 ). In this context, work stress includes stress related to health and safety risk, impaired performance, work adjustment, and negative emotions, for instance, such work stress can lead to unhealthy mental problems.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…People's motivations will learn to improvise, adapt and change consumer behavior. The long-term impact of COVID-19 has yet to be determined (Piccarozzi et al, 2021). Therefore, sued SARS describes from relevant literature on the epidemic's impact on the performance of medical institutions.…”
Section: Intrinsic Motivationmentioning
confidence: 99%